Strategi Pengembangan Produk UMKM melalui Batik Lokal Salem dalam meningkatkan Ekonomi Kreatif di Kabupaten Brebes - Hendri Sucipto; Nur Afridah; Elsara Khairun Nisa; Lidia Puput Mentari; Yunia Zahra Khaerunisa (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
The purpose of this study is to examine in-depth the product development strategies of MSMEs through local Salem batik to encourage the growth of the creative economy in Brebes Regency. Through a qualitative approach and case study analysis, this study will identify product innovation models, adaptive marketing strategies, and the role of collaboration between parties in strengthening the competitiveness of Salem batik. Thus, it is hoped that the results of this study can provide concrete recommendations for stakeholders to formulate more effective policies, empower Salem batik MSMEs, and ultimately, make Salem batik a primary driver of sustainable creative economic growth in Brebes Regency. The analysis tool used was SWOT. Based on the analysis results, the Total IFAS Score was 2.88 and the Total EFAS Score was 2.81. The SWOT analysis shows that the Salem Batik MSME has several prominent internal strengths, as reflected in the highest internal scores in categories 2, 3, 4, and 5. However, there are significant internal weaknesses in categories 6, 7, 8, 9, and 10, which require improvement. From the external side, there are strong opportunities, especially in categories 1 and 3, which can be utilized for growth. However, external threats also need to be watched out for, especially in categories 6, 7, 8, 9, and 10, where despite their low ratings, their high weighting makes these factors very influential and have the potential to become major obstacles or opportunities that have not been optimized. The main challenges faced include limited innovation, limited market reach, and the potential for minimal collaboration between partie.